Effect of Oxy-hydrogen Enrichment into Water-in-Biodiesel Emulsion Towards Performance and Exhaust Emissions of a Diesel Engine - Frendy Rian Saputro; Ahmad Muhsin Ithnin; Mohd Fareez Edzuan Abdullah; Chungpyo Hong; Takeshi Ohtaka; Aluyah Sipi; Wira Jazair Yahya (Bumi Publikasi Nusantara, 2026)
This study aims to evaluate the combined effect of water-in-biodiesel emulsions (WBE) and oxy-hydrogen (HHO) enrichment on diesel engine performance and emissions. Experiments were conducted on a single-cylinder diesel engine fueled with B35 (35% biodiesel–65% diesel), WBE5 (5% water-in-biodiesel emulsion), and their HHO-enriched blends under 1–4 kW loads. Engine performance was assessed through brake specific fuel consumption (BSFC), brake thermal efficiency (BTE), and exhaust gas temperature (EGT), while emissions of NOx, CO, and CO₂ were measured. Results show that WBE5 reduced NOx emissions by up to 30.2% compared with B35 and improved BSFC by 6.2% and BTE by 8.4% at 2–3 kW loads. However, CO emissions increased by about 18% due to lower combustion temperatures. HHO enrichment improved BSFC and BTE at light loads (1–2 kW) by up to 2% and decreased CO emissions through enhanced oxidation, but its influence on NOx was minimal and diminished at higher loads. Overall, WBE–HHO dual-fuel operation provides partial advantages, particularly under light-to-medium loads, offering a feasible pathway toward cleaner and more efficient diesel engine operation without major modifications.